2018
DOI: 10.1080/14767058.2018.1519542
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of reliability between uterocervical angle and cervical length measurements by various experienced operators using transvaginal ultrasound

Abstract: The UCA measurements had a higher intra- and interobserver reliabilities than the CL measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Accordingly, UCA measurements showed less variability compared to cervical length measurements. It was stated that UCA measurement is more reliable than cervical length measurement (22).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, UCA measurements showed less variability compared to cervical length measurements. It was stated that UCA measurement is more reliable than cervical length measurement (22).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Dagdeviren et al reported that patients with broader pre-induction UCAs were prone to have a shorter duration of the active phase [ 7 ]. Although a recent study reported that UCA combined with CL predicted labor induction more satisfactorily than CL alone, UCA is more reproducible than CL [ 21 , 23 , 24 ]. However, as an ultrasound parameter established relatively recently, only a few studies have examined the use of UCA in full-term pregnancies to predict IOL.…”
Section: Introductionmentioning
confidence: 99%